Age-dependent bone loss and recovery during hindlimb unloading and subsequent reloading in rats - Cunningham, Hailey C.; West, Daniel W. D.; Baehr, Leslie M.; Tarke, Franklin D.; Baar, Keith; Bodine, Sue C.; Christiansen, Blaine A. (BMC musculoskeletal disorders, 2018)
Background Bone structure and strength are rapidly lost during conditions of decreased mechanical loading, and aged bones have a diminished ability to adapt to increased mechanical loading. This is a concern for older patients that experience periods of limited mobility or bed rest, but the acute effects of disuse on the bones of aged patients have not been thoroughly described. Previous animal studies have primarily examined the effect of mechanical unloading on young animals. Those that have studied aged animals have exclusively focused on bone loss during unloading and not bone recovery during subsequent reloading. In this study, we investigated the effect of decreased mechanical loading and subsequent reloading on bone using a hindlimb unloading model in Adult (9 month old) and Aged (28 month old) male rats. Methods Animals from both age groups were subjected to 14 days of hindlimb unloading followed by up to 7 days of reloading. Additional Aged rats were subjected to 7 days of forced treadmill exercise during reloading or a total of 28 days of reloading. Trabecular and cortical bone structure of the femur were quantified using ex vivo micro-computed tomography (μCT), and mechanical properties were quantified with mechanical testing. Results We found that Adult rats had substantially decreased trabecular bone volume fraction (BV/TV) following unloading (− 27%) while Aged animals did not exhibit significant bone loss following unloading. However, Aged animals had lower trabecular BV/TV after 3 days of reloading (− 20% compared to baseline), while trabecular BV/TV of Adult rats was not different from baseline values after 3 days of reloading. Trabecular BV/TV of Aged animals remained lower than control animals even with exercise during 7 days of reloading and after 28 days of reloading. Conclusions These data suggest that aged bone is less responsive to both increased and decreased mechanical loading, and that acute periods of disuse may leave older subjects with a long-term deficit in trabecular bone mass. These finding indicate the need for therapeutic strategies to improve the skeletal health of elderly patients during periods of disuse.